Occupational Therapy to Improve Productivity of the Elderly by Creating Photo Frames at Panti Werdha Batam: Terapi Okupasi Untuk Meningkatkan Produktivitas Lansia Dengan Membuat Bingkai Photo Panti Werdha Batam - Rachmawaty M. Noer; Aprina Damaina; Belina Safitra; Devita Devita; Ernitha Ernitha; Nurazizah Nurazizah; Rosmian Rosmian; Septi Wijayanti; Sumarlini Sumarlini (Universitas Muhammadiyah Sidoarjo, 2023)
Aging is accompanied by physiological changes and an increased prevalence of acute and chronic diseases, leading to a decline in organ function and a reduced ability to adapt to environmental factors. Occupational therapy, encompassing activities related to personal care, recreation, and productivity, holds significance for individuals. This study aimed to identify the needs and analyze the situation of elderly residents at the Budi Sosial Foundation's Elderly Home. The four-stage methodology involved situational analysis, health assessments, and physical activity education sessions. The implementation phase included simulation and assistance, where participants were engaged in arranging popsicle sticks into frame shapes. Monitoring and evaluation were conducted to assess the effectiveness of the health assessments and physical activity education, with all 17 (100%) active elderly participants observed. The results demonstrate the potential benefits of occupational therapy in promoting physical activity and overall health among elderly individuals. These findings imply the importance of integrating occupational therapy interventions to enhance the well-being and functional abilities of the elderly population. Highlights: Occupational therapy: A beneficial intervention for elderly individuals' well-being and functional abilities. Physical activity promotion: Enhancing the overall health and adaptability of the aging population. Health assessment: Evaluating the effectiveness of occupational therapy interventions in elderly care. Keywords: aging, occupational therapy, physical activity, health assessment, elderly population